Dabigatran Etexilate and Risk of Myocardial Infarction, Other Cardiovascular Events, Major Bleeding, and All‐Cause Mortality: A Systematic Review and Meta‐analysis of Randomized Controlled Trials. Issue 3 (6th June 2014) - Douxfils, Jonathan; Buckinx, Fanny; Mullier, François; Minet, Valentine; Rabenda, Véronique; Reginster, Jean‐Yves; Hainaut, Philippe; Bruyère, Olivier; Dogné, Jean‐Michel
Abstract : Background: Signals of an increased risk of myocardial infarction (MI) have been identified with dabigatran etexilate in randomized controlled trials (RCTs). Methods and Resules: We conducted searches of the published literature and a clinical trials registry maintained by the drug manufacturer. Criteria for inclusion in our meta‐analysis included all RCTs and the availability of outcome data for MI, other cardiovascular events, major bleeding, and all‐cause mortality. Among the 501 unique references identified, 14 RCTs fulfilled the inclusion criteria. Stratification analyses by comparators and doses of dabigatran etexilate were conducted. Peto odds ratio (ORPETO ) values using the fixed‐effect model (FEM) for MI, other cardiovascular events, major bleeding, and all‐cause mortality were 1.34 (95% CI 1.08 to 1.65, P =0.007), 0.93 (95%CI 0.83 to 1.06, P =0.270), 0.88 (95% CI 0.79 to 0.99, P =0.029), and 0.89 (95% CI 0.80 to 1.00, P =0.041). When compared with warfarin, ORPETO values using FEM were 1.41 (95% CI 1.11 to 1.80, P =0.005), 0.94 (95%CI 0.83 to 1.06, P =0.293), 0.85 (95% CI 0.76 to 0.96, P =0.007), and 0.90 (95% CI 0.81 to 1.01, P =0.061), respectively. In RCTs using the 150‐mg BID dosage, the ORPETO values using FEM were 1.45 (95% CI 1.11 to 1.91, P =0.007), 0.95 (95% CI 0.82 to 1.09, P =0.423), 0.92 (95% CI 0.81 to 1.05, P =0.228), and 0.88 (95% CI 0.78 to 1.00, P =0.045), respectively. The results of the 110‐mg BID dosage were mainly driven by the RE‐LY trial. Conclusions: This meta‐analysis provides evidence that dabigatran etexilate is associated with a significantly increased risk of MI. This increased risk should be considered taking into account the overall benefit in terms of major bleeding and all‐cause mortality.